Assessment of the impact of trade openness on economic growth: Case of Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
This paper examines the growth effects of trade openessin sub-Saharan countries. We used Generalized method of moments GMM to analyze the data of 38 years (1981-2019). Our results show that trade openness has a significant impact on economic growth. During the reporting period, population growth and physical capital were among the main determinants of economic growth.
Keywords: African Research